Almanac 2014: congenital heart disease. Issue 1 (12th December 2014) - Kahr, Peter C; Diller, Gerhard-Paul
Abstract : This Almanac summarises important congenital heart disease articles published between 2012 and 2014 in Heart and other major cardiac journals. It highlights what the authors perceive to be highly relevant articles in the field. While the aim was to provide a comprehensive overview of the area, a focus on certain areas of interest was required. The selection is, therefore, by necessity a subjective one.